Women's perception of prenatal and delivery care in cases of neonatal death - Maria Aparecida Munhoz Gaíva; Ellen Whate Morais Palmeira; Leandro Felipe Mufato (Universidade Federal do Rio de Janeiro, 2017)
Abstract Objective: To analyze women's perception of care in prenatal and delivery care in cases of neonatal death. Method: A qualitative study was carried out with women whose children died in the neonatal period. Data were collected through open-ended interviews and analyzed according to the thematic analysis technique. Results: The professional-patient relationship in which there is dialogue is associated with good prenatal experience for women. Guidelines and information about health are seen as a positive aspect to achieve quality of care. The difficulty of access to exams and the lack of preparation of women for childbirth appear as negative aspects for care. Conclusions: Negative health care factors are reflected in a biographical way on these women. Implications for practice: Include results that can serve as a warning for professionals who provide care for pregnant and parturient women.